Application of the principles of Semantic Web and Linked Data to TV broadcasting archives. Backround and perspectives. - Soler Monreal, Concha; Gil Leiva, Isidoro (Revista General de Información y Documentación, 2023)
This article addresses the application of Semantic Web technologies to TV broadcasting archives. From a general perspective, an approach is presented for the implementation of Linked Data to TV broadcasting archives with the aim of optimizing and reusing resources both for the management of information and for the broadcast of the multimedia products of the media. The process is carried out at every stage of the documentary chain in two directions: inside the archive, to improve the metadata, and outside, through the media’s publications, to control access to second screens and, thus, prevent the viewer from getting distracted. Linked Data projects developed by the media as well as by broadcasting archives re listed, and new methods for reusing resources are proposed.
Keywords: semantic web; linked data; broadcasting archives; audiovisual archives; documentary chain; second screens; metadata